Apple Training Series iLife '06 - Rubin, Michael (Peachpit Press, 2006)
In the only Apple-certified guide to iLife '06, you will be making miracles with iLife within the first few pages. Using real-life material and practical lessons that you can apply immediately to your own projects, this book/DVD combo offers a complete, self-paced course in all aspects of iLife '06. Focused lessons take you step-by-step through everything from arranging your iTunes library to creating Hollywood-style movies using motion titles. Fully updated to cover all the new features of iLife '06 including the brand new iWeb application, this book will take you from newbie to producer of your own media content in one day! The book is both a self-paced learning tool and the official curriculum of the Apple Training and Certification Program, used by schools and training centers worldwide. An easy, accessible style paired with ample illustrations and keyboard shortcuts guarantee that readers will make iLife their life in no time.